Effect Of Lavender Oil Aromaterapy On Menstrual Pain In Students AT SMPN18 PESAWARAN In 2020 - Eby Juliana Sabrina; Riona Sanjaya; Surmiasih; Yona Desni Sagita (Biomedical Journal of Indonesia, 2020)
The problem of primary dysmenorrhoea is largely overcome by resting and taking medication. Many ways to eliminate or reduce dysmenorrhea both pharmacologically and non-pharmacologically. Management of menstrual pain can also be managed nonpharmacologically, such as giving aromatherapy, aromatherapy administration techniques can use a variety of aromatherapy such as lavender. The purpose of this study was to determine the effect of Lavender Oil Aromatherapy on Menstrual Pain in Students at SMP N 18 Pesawaran in 2020. This type of quantitative research design is quasy experimental design research with one grub pretest and posttest approach. The population in this study were all students. Samples taken in this study were 31 students who experienced disminore when the study took place. Analysis of the data used using the Wilcoxon test. The results of data analysis and processing found that there was an effect of Lavender Oil Aromatherapy on Menstrual Pain in Junior High School 18 Pesawaran in 2020 with a p-value of 0,000 <0.05. Respondents can increase their knowledge about handling disminorea by searching for information via the internet or reading books, so that respondents are not dependent on pharmacological treatment alone.